Couple-stress nanofluid flow comprised of titanium alloy subject to Hall current and Joule heating effects: Numerical investigation - Jubair, Sidra; Ali, Bilal; Rafique, Khadija; Ahmad Ansari, Mushtaq; Mahmood, Zafar; Kumar, Abhinav; Mukalazi, Herbert; Alqahtani, Haifa (AIP advances, 2024)
Nanofluid flow over a rotating disk has several applications in engineering and industrial sectors, such as in cooling systems, heat exchangers, aerospace systems, and renewable energy systems. In the current analysis, the couple stress nanofluid flow over a rotating disk is reported. The nanofluid consists of ethylene glycol and titanium aluminum vanadium (Ti6Al4V) nanoparticles (NPs). The unique properties of Ti6Al4V-NPs, such as biocompatibility, high strength, high boiling point (1604–1660 °C), and high corrosion resistance, make them more suitable for automobile industries. For the heat and mass transfer, the Cattaneo–Christov concept is introduced. In addition, the fluid flow is subjected to magnetic field, Hall current, thermal radiation, and Joule heating. The modeled equations are restructured into the dimensionless system of ordinary differential equations (ODEs) by using the similarity approach. The system of ODEs is further numerically solved through a MATLAB package based on the finite difference method (BVP4c). The results are presented in figures. It has been observed that the energy and curves of the nanofluid decline with the influence of thermal and solutal time relaxation parameters, respectively.